Adsorption, X-ray diffraction, photoelectron, and atomic emission spectroscopy benchmark studies for the eighth industrial fluid properties simulation challenge - Richard B Ross; David B Aeschliman; Riaz Ahmad; John K Brennan; Myles L Brostrom; Kevin A Frankel; Jonathan D Moore; Joshua D Moore; Raymond D Mountain; Derrick M Poirier; Matthias Thommes; Vincent K Shen; et al. (Adsorption Science & Technology)
The primary goal of the eighth industrial fluid properties simulation challenge was to test the ability of molecular simulation methods to predict the adsorption of organic adsorbates in activated carbon materials. The challenge focused on the adsorption of perfluorohexane in the activated carbon standard BAM-P109. Entrants were challenged to predict the adsorption of perfluorohexane in the activated carbon at a temperature of 273 K and at relative pressures of 0.1, 0.3, and 0.6. The relative pressure (P/P o ) is defined as that relative to the bulk saturation pressure predicted by the fluid model at a given temperature (273 K in this case). The predictions were judged by comparison to a set of experimentally determined values, which are published here for the first time and were not disclosed to the entrants prior to the challenge. Benchmark experimental studies, described herein, were also carried out and provided to entrants in order to aid in the development of new force fields and simulation methods to be employed in the challenge. These studies included argon, carbon dioxide, and water adsorption in the BAM-P109 activated carbon as well as X-ray diffraction, X-ray microtomography, photoelectron spectroscopy, and atomic emission spectroscopy studies of BAM-P109. Several concurrent studies were carried out for the BAM-P108 activated carbon. These are included in the current manuscript for comparison.